Compensador série controlado a tiristores na distribuição: Compensação dinâmica - Almeida, Patrick Roberto de [UNESP] (2014)
FACTS controllers (Flexible Alternating Current Transmission Systems) are capable of modifying the natural parameters of a transmission system to operate closed to the rated limits and delaying investments in the expansion these systems. In general, such devices can be series connected, shunt or a combination of both, allowing the correction of power system stability problems, voltage sags and swells, and others. In distribution systems, the reactive compensators, especially switched series capacitor banks and shunt capacitor banks as well as electronic controllers for many different purposes, has changed the classical topology, typically passive. For example, the thyristor controlled series compensators emerge as an alternative to fixed series compensation, allowing postpone of investments in distribution networks, substations, etc. This dissertation presents the D-TCSC (Distribution - Thyristor Controlled Series Compensator), a FACDS (Flexible Alternating Current Distribution Systems) controller which can be used as a solution to voltage control during connection of large loads, according the voltage levels established by PRODIST - Distribution Procedure